2004
DOI: 10.1002/eat.10257
|View full text |Cite
|
Sign up to set email alerts
|

The sociocultural attitudes towards appearance scale‐3 (SATAQ‐3): Development and validation

Abstract: The SATAQ-3 measures multiple aspects of a societal influence and should prove useful for basic risk factor work as well as for gauging the efficacy of prevention and treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
737
3
70

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 934 publications
(842 citation statements)
references
References 16 publications
32
737
3
70
Order By: Relevance
“…This scale has demonstrated reliability and validity, and is widely used, among adults and adolescents (Thompson et al, 2004). Internal consistency in the current study was good (Cronbach's α= .95 and .94 for mothers and daughters, respectively).…”
Section: Intervention Outcomesmentioning
confidence: 56%
“…This scale has demonstrated reliability and validity, and is widely used, among adults and adolescents (Thompson et al, 2004). Internal consistency in the current study was good (Cronbach's α= .95 and .94 for mothers and daughters, respectively).…”
Section: Intervention Outcomesmentioning
confidence: 56%
“…Media-ideal internalization: the 9-item General (e.g., "I don't try to look like the people on TV"; reverse item) and the 5-item Athletic Internalization (e.g., "I don't wish I looked as athletic as the people in magazines"; reverse item) subscales of the Italian version [59,60] of the Sociocultural Attitudes Toward Appearance Questionnaire-3 (SATAQ-3) [61] were used to assess media-ideal internalization at T1. Research indicated that both subscales are critical in measuring females' and males' endorsement of media messages that espouse unrealistic body shape ideals and the striving toward such ideals see [18].…”
Section: Methodsmentioning
confidence: 99%
“…Media internalization* Sociocultural Attitudes Towards Appearance Questionnaire-3, (Thompson, et al, 2004) 30-items (Girls  =.96; Boys  =.97) e.g., I compare my body to the bodies of TV and movie stars, 1= "definitely disagree" to 5 = "definitely agree"…”
Section: Discussionmentioning
confidence: 99%
“…The CDI is the most commonly used measure of depressive symptomatology in depression studies with children and adolescents (Horowitz & Garber, 2006) and has been reliably used with early adolescent Australian Depression as a moderator samples (Roberts, Kane, Thomson, Bishop, & Hart, 2003). The validity and reliability of the Sociocultural Attitudes Towards Appearance Questionnaire-3 (Thompson, van den Berg, Roehrig, Guarda, & Heinberg, 2004) as a measure of media internalization has been previously confirmed with young-adolescent Australian girls and boys (Wilksch & Wade, 2012). Finally, the Eating Disorder Inventory -Body Dissatisfaction scale (Garner, Olmstead, & Polivy, 1983) is widely used in eating disorder research and has been found to be reliable and valid measure for 11-18-year-old participants (Shore & Porter, 1990).…”
Section: Methodsmentioning
confidence: 99%